Program Kampus Mengajar (ProKM) sebagai Upaya Peningkatan Pembelajaran Siswa Di SMP Muhammadiyah 12 Paleran, Umbulsari - Erika Anugra Heni; Arik Susbiyani; Imam Bukhori Muslim; Moh. Qurtubi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2023)
This study aims to find out how the role of the Teaching Campus in improving the literacy, numeracy and technological adaptation of the first menegah school students in East Java to improve the quality of education. This research uses a descriptive qualitative approach. The study was conducted for six months. The location of this study was carried out at the Junior High School in East Java, namely SMP Muhammadiyah 12 Paleran. Data collection procedures, techniques and instruments using observation, interviews and documentation. So it can be concluded that the Teaching Campus in improving literacy, numeracy and technology adaptation has an important and successful role in carrying out its programs assisted by students and the support of the school and students.